PARTICIPATION INFLUENCES DEVELOPMENT - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Following a conference in Panama in 1992, the six countries of the Central American Isthmus decided to set up a programme aimed at enabling ordinary people in the food industry to participate fully in the development process. Communication at all...